Dimensi edukatif peran keluarga dalam pengembangan integritas kepribadian anak menurut Al-Qur’an - Inzah, M. (LP3M UNZAH GENGGONG, 2024)
In this research, it aims to create a strong and high-quality future generation for the nation; parents must make consistent and continuous efforts to look after their children both physically and mentally as well as nurturing, nurturing and nurturing them until they become parents. Child to reach adulthood and /or can be alone if this task is the parent's responsibility. The issue of parenting and education is about ensuring the welfare of children, which aims to improve the quality of children's growth and development and avoid oppression and unfair treatment, so that children become perfect, tough, intelligent and virtuous children. The human protection of a child is the parents. In society, the family is the smallest unit that plays a very important role. This enormous role cannot be separated from the fact that the family has a very important role in the survival of society. Knowledge about the rules and values adhered to is first obtained in the family.